Habilidades sociales y la convivencia democrática en estudiantes del primer año de secundaria de la Institución Educativa Primaria y Secundaria N°60239 San Francisco de Asís, Pebas 2025 - Torres Inuma, Smith (2025)
The purpose of this research was to determine the relationship between social skills and democratic coexistence in first-year secondary school students at the San Francisco de Asís Primary and Secondary School No. 60239, Pebas 2025. The study had a quantitative, basic, non-experimental, cross-sectional design, and the sample consisted of 60 first-year secondary school students. The findings showed that 41.7% of the students had poor social skills, while 51.7% of the students had poor democratic coexistence skills. The results of Spearman's Rho test show a high positive correlation of 0.722 and a significance of p=0.000 between the variables, concluding that there is a significant relationship between social skills and democratic coexistence in first-year secondary school students at the Primary and Secondary Educational Institution No. 60239 San Francisco de Asís, Pebas 2025.